Pendampingan siswa sadar gizi dalam upaya pencegahan kurang gizi pada anak sekolah di MIN 8 Aceh Besar - Wagustina, Silvia; Arnisam, Arnisam; Fitriyaningsih, Eva; Novita, Rosi (Jurnal PADE: Pengabdian & Edukasi, 2024)
School children (AS) are one of the groups that are vulnerable to nutritional and health disorders. Balanced nutrition is needed in the process of child growth and development, improving good learning abilities, and providing a positive impact on their development in the future. The prevalence of children aged 6-12 years in Indonesia who are underweight (wasting) and very underweight using the BMI/U indicator is 7.6% and 4.6%. One of these nutritional problems can be caused by low nutrient intake both in the past and in the present. This community service activity is to increase school children's knowledge about nutrition and health in an effort to prevent and overcome malnutrition in school children. The selection of school nutrition cadres (KGS) was carried out as role models for healthy school children and had the task of assisting school teachers in implementing TBAS measurements. Providing nutrition education is done through lectures and questions and answers, the media used are power points and leaflets. Knowledge of nutrition and health of school children is assessed before and after providing nutrition education. In this activity, TBAS measurements were carried out. Results: Before being given nutrition education, most of the nutritional and health knowledge of school children was low (76,5%), most of the AS did not eat breakfast (38,2%). The results of the TBAS measurement were partly short, namely boys by 51,3% and girls by 27,1%. Conclusion: There was an increase in student knowledge after being given nutrition education by 34,4%.